Bordering biomedicine - Kalitzkus, Vera; Twohig, Peter (At the interface/probing the boundaries, 2006)
Biomedicine is the dominant organizing framework of modern medicine but it is not the only lens through which health, illness and disease can be understood. This interdisciplinary collection of essays brings together scholars from around the world who seek to probe the boundaries of biomedicine. This book is the outcome of the third global conference on "Making Sense of: Health, Illness and Disease," held at St Catherine's College, Oxford, in July 2004. The papers selected for this volume take a variety of theoretical positions but share an interest in the social study of health, ill.